Effect of different post-harvest processing on the sensory profile of Java Arabica coffee - Wenny B. Sunarharum; Sudarminto S. Yuwono; Hasna Nadhiroh (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2018)
Coffee consumption in the world is continuously growing and demanding high quality. Coffee cup quality is a complex matters involving several factors that includes post-harvest processing factor. The objective of this research is to investigate the impact of different coffee post-harvest processing methods i.e. fermentation methods (natural/dry, semi-washed and fully-washed processing), and drying methods (mechanical and sun drying) on the sensory quality of Java Arabica medium-roasted coffee beans. The sensory quality was evaluated through cupping test employing five expert judges. The result revealed that different post-harvest processing factors has a significant influence on coffee sensory quality, particularly on four cupping attributes, namely fragrance/aroma, flavour, defects and final scores. Fermentation using more water and controlled mechanical drying were found to yield a better coffee sensory profile due to less identified defective characters in the cup. Nevertheless, different processing created specific coffee character that would have its own market provided the quality is properly controlled.